EMPLOYERS’ ASSESSMENT OF PROGRAM EDUCATIONAL OBJECTIVES: A SURVEY-BASED EXPLORATION FOR DIPLOMA IN INFORMATION TECHNOLOGY (DIGITAL TECHNOLOGY) - Jacey Mariadass; ‘Afifah Nailah Muhamad; Aminah Bibi Bawamohiddin (Journal of Islamic, Social, Economics and Development, 2023)
The field of Information Technology (IT) is essential for fostering innovation and growth in the economy. Education institutions must make sure that their curricula meet business needs and adequately educate graduates for the workforce as the need for qualified IT experts emerges. Programme Educational Objectives (PEOs) act as a critical component of curriculum design and assessment, outlining the intended outcomes and goals of an educational program. However, there is a lack of research exploring employers' assessment of PEOs specifically in the Diploma in Information Technology (Digital Technology) program. This study aims to bridge this gap by conducting a survey-based exploration of employers' perspectives on PEOs. This study involved a total of 77 respondents. The findings provide valuable insights for curriculum improvement, enhancing the relevance of the program and better meeting the needs of the job market. Ultimately, the study contributes to the ongoing dialogue on the quality and relevance of IT education and empowers institutions to produce graduates equipped with the necessary skills for success in the digital technology industry.